2022
DOI: 10.5603/pjnns.a2022.0060
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate metabolism and lipid profile in patients with Parkinson’s disease with subthalamic deep brain stimulation

Abstract: Aim of the study. Assessment of potential effect of subthalamic nucleus deep brain stimulation (STN-DBS) on glucose metabolism in patients with Parkinson's disease (PD).Clinical rationale for the study. Although a valuable alternative to pharmacotherapy in advanced PD, STN-DBS is thought to negatively affect the cardiometabolic profile of patients (including body mass, lipid profile). Exacerbation of glucose metabolism dysregulation after DBS could therefore be assumed. Material and methods.Two groups of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A possible association between lipid metabolic changes and parkinsonism has also been described in the context of Parkinson's disease and deep brain stimulation therapy (DBS) [32]. The authors indicated that the DBS group was characterised by increased BMI and TG levels and decreased HDL-C levels.…”
Section: Discussionmentioning
confidence: 98%
“…A possible association between lipid metabolic changes and parkinsonism has also been described in the context of Parkinson's disease and deep brain stimulation therapy (DBS) [32]. The authors indicated that the DBS group was characterised by increased BMI and TG levels and decreased HDL-C levels.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, we speculate that autonomic dysfunction and STN-DBS may have a pivotal role in decreased tears production in such patients. Moreover, a "burning sensation in the eye" may be considered, among others, an ocular adverse effect after STN-DBS in PD patients [14,15]. Reduced contrast sensitivity, which is a common symptom in PD, is not yet fully understood [6].…”
Section: Discussionmentioning
confidence: 99%
“…Choosing between these targets is based on institutional preference and/or, more importantly, patient characteristics. Elsewhere in this issue, Samborska-Ćwik et al have reported weight gain and several negative metabolic consequences in PD patients who underwent STN DBS [9]. These may represent direct stimulation-related effects and/or indirect consequences of DBS clinical effects, e.g.…”
mentioning
confidence: 99%
“…The recent work by Samborska-Ćwik et al [9] has begun to untangle the complex cascade of glycaemic control in PD and how it is altered with DBS. While most work in this field has focused on weight changes and glucose effects, these authors have begun to uncover changes in the metabolism of other macromolecules, e.g.…”
mentioning
confidence: 99%